Migrating humpback whales (Megaptera novaeangliae) do not respond to underwater construction or whale alarms off Sydney, Australia - Vanessa Pirotta (2017)
Humpback whales (Megaptera novaeangliae) migrating along the east coast of Australia are exposed to a multitude of anthropogenic activities. We investigated the effects of two types of activities migrating humpback whales are exposed to within the whale migratory corridor off Sydney; (1) fisheries mitigation and (2) underwater construction. Observational and spatial data were collected during the 2008 and 2013 northern migration off Sydney. Whale surface behaviour and directionality was compared between presence and absence of two types of ‘whale’ alarm (3kHz Future Oceans F3™ tone or 2-2.1kHz swept tone) and secondly in the presence or absence of underwater construction. A total of 254 tracks (146 in 2008, 108 in 2013) were collected using a theodolite. There was no detectable response to the whale alarm. Pods did not differ in directionality or surfacing behaviour whether the alarm was on or off.Whales exhibited no response to construction activities in 2008 (days with/without construction) and were no different five years post construction except that dive duration was longer in 2013. This study points to inadequacies in using acoustic alarms as a mitigation measure and is the first to assess the effects of actual underwater construction on thebehaviour of migrating humpback whales.